Entry Mode Choice of Multinational Banks - Maria Lehner (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
When expanding abroad, a multinational bank faces a trade-off between accessing a foreign country via cross border lending or a financial foreign direct investment, i.e. greenfield or acquisition entry. We analyze the entry mode choice of multinational banks and explicitly derive the entry mode pattern in the banking industry. Moreover, we show that in less developed banking markets, a trend towards cross border lending and acquisition entry exists. Greenfield entry prevails in more developed markets. Furthermore, we identify a tendency towards acquisition entry in small and towards greenfield entry in larger host countries.
urn:nbn:de:bvb:19-epub-8222-5
Keywords: F37; G21; G34; L13; O16; 330; foreign bank entry; multinational bank; cross border lending; greenfield entry; acquisition entry; Internationaler Markteintritt; Internationale Bank